Akademicka obyczajowość - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2023)
Customs are powerful environmental determinants that shape and separate one group from many others, often taking generations to evolve. When it comes to academia, it is no different. From the founding of the first universities to our present day, there have been two major components of academic morality that have undergone significant changes: academic institutionalism and academic dissemination of knowledge and skills. It can be difficult to adjust to such changes, especially when certain practices once served our predecessors well but their time has passed. However, with the right mindset and an openness to learning from the past and improving on it, we can ensure that our next colleagues will make the most of what their predecessors have left behind and take their knowledge and skills to the next level.